BASELINE STUDY OF DIVERSITY AND INSECT SPECIES RICHNESS RECORDED IN FEDERAL UNIVERSITY DUTSIN-MA TAKE -OFF CAMPUS, KATSINA, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2025)
Worldwide, University campuses are increasingly mandating ecosystem preservation and conservation into their practices. The study investigated the diversity and species richness of insects at the Take-off Campus of Federal University Dutsin-Ma, Katsina State. Two sites, the Clinic and ICT complex were chosen to reflect the level of anthropogenic disturbance. Insects were collected using the light trap methodology. Data collected was analyzed using the Shannon-Weiner diversity index, Simpson index of diversity, and Equitability Index on the PAST Program. Results showed that both locations had an identical insect species richness of 13. However, the clinic hosted a higher number of individual insects (101) compared to the ICT Complex (67). Diversity indices revealed that the ICT Complex had slightly higher values for the Simpson index (0.91) and Shannon index (2.50), indicating greater diversity and more ecosystem services. The equitability index was also higher at the ICT Complex (0.97). The findings highlighted the ecological health of the study area and underscore the importance of adopting Integrated Pest Management (IPM) strategies to manage pests while preserving beneficial insects to ensure ecological sustainability and promote a balanced campus environment.
Keywords: Diversity; Insects; Species richness; Carpenter ant; Dutsin-Ma; Nigeria